In
order to solve for a nth term in an arithmetic sequence, we use the formula
written as:<span>
an = a1 + (n-1)d
where an is the nth term, a1 is the first value
in the sequence, n is the term position and d is the common difference.
First, we need to calculate for d from the given
values above.
<span>a3 = 20.5 and a8 = 13
</span>
an = a1 + (n-1)d
20.5 = a1 + (3-1)d
</span>an = a1 + (n-1)d
13 = a1 + (8-1)d
<span>
a1 = 23.5
d = -1.5
The 11th term is calculated as follows:
a11 = a1 + (n-1)d
a11= 23.5 + (11-1)(-1.5)
a11 =
8.5</span>
4x + 3 = 11
4x = 11 -3
4x = 8
x =8/4
x =2
answer
the number is 2
Answer:
<h2>d=(14,0)</h2>
Step-by-step explanation:
<h2>√(7-(-7))^+(4/19-4/19)^</h2><h2>√(7+7)^+(0)^</h2><h2>√(14)^+0</h2><h2>= 14</h2>